Chemical Stability of FeOOH at High Pressure and Temperature, and Oxygen Recycling in Early Earth History. Issue 30 (28th June 2021) - Koemets, Egor; Fedotenko, Timofey; Khandarkhaeva, Saiana; Bykov, Maxim; Bykova, Elena; Thielmann, Marcel; Chariton, Stella; Aprilis, Georgios; Koemets, Iuliia; Glazyrin, Konstantin; Liermann, Hanns‐Peter; Hanfland, Michael; et al.
Abstract: Goethite, α‐FeOOH, is a major phase among oxidized iron species, commonly called rust. We studied the behavior of iron (III) oxyhydroxide up to 81 GPa and 2100 K using in situ synchrotron single‐crystal X‐ray diffraction. At high pressure‐temperature conditions FeOOH decomposes forming oxygen‐rich fluid and different mixed valence iron oxides (previously known phases of Fe2 O3, Fe3 O4, Fe5 O7, and novel Fe7 O10 and Fe6.32 O9 ). Rust is known to form as a byproduct of anoxygenic prokaryote metabolism that took place massively from about 3.8 billion years (Ga) ago until the Great Oxidation Event (GOE) ∼2.2 Ga ago. Rust was buried on the ocean floor and was transported into the mantle as a consequence of plate tectonics (started ∼2.8 Ga ago). Our results suggest that recycling of rust in Earth's mantle contributes to redox conditions of the early Earth and formation of oxygen‐rich atmosphere. Abstract : We report a detailed investigation of the stability field of FeOOH at extreme pressures and temperatures corresponding to lower mantle conditions. We observed decomposition of FeOOH with a formation of a series of high‐pressure iron oxides, including two novel ones, Fe7 O10 and Fe6.32 O9 . We discuss their structures and the role of FeOOH decomposition in the Earth's oxygen cycle.